2020
DOI: 10.1155/2020/7893023
|View full text |Cite
|
Sign up to set email alerts
|

Catastrophizing Has a Better Prediction for TMD Than Other Psychometric and Experimental Pain Variables

Abstract: Temporomandibular disorders (TMDs) are characterized by moderate to severe pain in the masticatory muscles and/or the temporomandibular joint (TMJ). The present study is a part of a multidisciplinary project, initiated by the Norwegian Ministry of Health. The main purpose of this study is to compare a cohort of TMD patients to healthy individuals regarding experimental pain, the degree of disability caused by living with pain and psychometric variables, and to investigate which of these variables is the best p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 47 publications
1
13
0
1
Order By: Relevance
“…A description of the interdisciplinary work up and a characterization of the patient group with severe TMD has previously been published. 11,12,16,30,31 Three-Year Follow Up Three years after the interdisciplinary evaluation, the patients received a comprehensive questionnaire by mail, similar to the questionnaire that they had filled in at the first evaluation with the addition of questions regarding their satisfaction with the follow-up by their GMP. Further, there were questions regarding the progression of their TMD symptoms (on a five-point scale, from much improved to much worse) and general health symptoms (on a three-point scale, from improved to worse), what kind of treatments they had received and the outcome of the treatments.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…A description of the interdisciplinary work up and a characterization of the patient group with severe TMD has previously been published. 11,12,16,30,31 Three-Year Follow Up Three years after the interdisciplinary evaluation, the patients received a comprehensive questionnaire by mail, similar to the questionnaire that they had filled in at the first evaluation with the addition of questions regarding their satisfaction with the follow-up by their GMP. Further, there were questions regarding the progression of their TMD symptoms (on a five-point scale, from much improved to much worse) and general health symptoms (on a three-point scale, from improved to worse), what kind of treatments they had received and the outcome of the treatments.…”
Section: Participantsmentioning
confidence: 99%
“…Chronic stress in patients with TMD has been considered an important characteristic of TMD, as previously shown by high CSQ and HADS scores. 11,12,39 Psychosocial factors, including stress, have also been considered as a major risk factor in TMD, 1,10,40 in the development of chronic pain. 41 Elevated CSQ may indicate poorer prognosis for pain relief in chronic pain in general.…”
Section: Journal Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Axis II core assessment aspects of both RDC/TMD and DC/TMD are psychological distress (eg depression and anxiety), somatisation and pain‐related disability. In addition to psychological distress and somatic symptoms, recent OPPERA studies and numerous studies identified pain catastrophising and maladaptive cognitive error of pain perception, as potent psychometric factors for TMD pain and disability 2,7 8 …”
Section: Introductionmentioning
confidence: 99%
“…In addition to psychological distress and somatic symptoms, recent OPPERA studies and numerous studies identified pain catastrophising and maladaptive cognitive error of pain perception, as potent psychometric factors for TMD pain and disability. 2,7 Kinesiophobia, another important psychometric dimension for assessing fear of movement, is a strong predictor of disability in patients with musculoskeletal disorders, including TMD. 8 In addition to pain, jaw functional limitation, included in Axis II of RDC/TMD and DC/TMD, is another major negative impact of TMD.…”
mentioning
confidence: 99%